Comparison of three port placement strategies for robot-assisted laparoscopic lich-gregoir direct nipple ureteral extravesical reimplantation in pediatric primary obstructive megaureter: multi-ports, single-port-plus-one, single-port - Zhang, Yuru; Lu, Jingjing; Lin, Shan; He, Shaohua; Xu, Di; Chen, Jianglong (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the efficacy, safety, and cosmetic outcomes of three robot-assisted laparoscopic techniques for treating pediatric primary obstructive megaureter (POM): robot-assisted laparoscopic multi-ports (RLMG), robot-assisted laparoscopic single-port-plus-one (RLSPG), and robot-assisted laparoscopic single-port (RLSG).Materials and methodsA retrospective analysis included 30 pediatric POM patients (December 2022–December 2024) undergoing Da Vinci Xi robotic Lich-Gregoir ureteral reimplantation. Patients were categorized into RLMG (n = 13), RLSPG (n = 10), and RLSG (n = 7) groups based on incision methods. Preoperative assessments, Intraoperative parameters, postoperative outcomes, and hydronephrosis metrics were analyzed using SPSS 21.0, with significance set at P < 0.05.ResultsThere were no significant differences in baseline demographic characteristics. There were significant inter group differences in the distribution of surgical side (P = 0.005). In terms of total surgical time, the RLMG group was significantly shorter than the RLSPG and RLSG (P = 0.02). There was no significant difference in ureteral reimplantation time among the three groups (P = 0.85), but the ratio of ureteral reimplantation time to total surgical time in the RLSPG and RLSG was significantly lower than that in the RLMG (P < 0.001). The Stony Brook Scar Evaluation Scale (SBSES) score showed that the RLSG had significantly higher scores than the RLMG (P = 0.009) and RLSPG (P = 0.244). After surgery, only 2 cases of RLMG, 3 cases of RLSPG, and 2 cases of RLSG developed urinary tract infections, all of which were relieved through conservative treatment without recurrence. In terms of follow-up time, the RLMG had the longest median follow-up time, with significant differences between groups (P < 0.001). The relief rate of obstruction in all three groups was 100%. Postoperative renal hydronephrosis parameters were significantly improved compared to preoperative levels (P < 0.001).ConclusionRobot-assisted laparoscopic ureteral reimplantation is a safe and effective treatment for pediatric POM. The single-port approach achieves superior cosmesis, whereas the multi-ports technique affords the shortest operative time. The single-port-plus-one offers a balanced intermediate option, enabling surgeons to optimize outcomes based on patient and procedural needs.